(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Genotoxic effect of 10 days old culture filtrate of a soil borne fungal pathogen i.e. Rhizoctonia salani were evaluated in root meristem cells of Allium cepa so as to assess the level of Genotoxicity. In the Allium root growth test the effective concentration i.e. 10 days old culture filtrate was determined significant. Mitotic index of the root meristem treated under culture filtrate was observed to be statistically significant after 120h treatment, marked genotype abnormalities i.e. stickiness, bridge, vagrant, multipolarity, c-Anaphase were also records during the investigation.